Education Spillovers and Labor Productivity Convergence In Yogyakarta Special Region and Central Java - Susanto, Joko; Udjianto, Didit Welly (Proceeding UII-ICABE, 2020)
This study aims to identify the possibility of the occurrence of education spillover and the convergence of labor productivity in the Yogyakarta Special Region and Central Java. The research data includes the expected year of schooling, GRDP per capita, the number of senior high school, poverty rate, and labor productivity published by the Central Bureau of Statistics (BPS). The data were analyzed by the spatial regression models and the coefficient of variation. The results indicate that there is an education spillover. The expected years of schooling in a region/city is not only influenced by causal factors in this area but also influenced by the expected years of schooling in the surrounding area. Education spillover encourages an increase in labor productivity in the lagging region faster than advanced ones so that they are capable of catching up. Therefore, education spillover promotes convergence in labor productivity. Keywords: education, spillovers, labor, productivity, Convergence